A novel adjustable reversible data hiding method for AMBTC-compressed codes using Hamming distance. (23rd September 2021) - Xia, Ting-Ting; Lin, Juan; Chang, Chin-Chen; Lu, Tzu-Chuen
In this paper, we propose a novel adjustable reversible data hiding method for AMBTC-compressed codes using Hamming distance. First, the original image is compressed by AMBTC technique to obtain two quantisation levels and a bitmap of each block. Next, the scheme converts the bitmap of each block to a decimal number and calculates the frequency of the decimal number to find the maximum frequency of the decimal number as the peak bitmap. In our scheme, if the block is equal to the peak bitmap, then the block is embeddable. The scheme generates a candidate list to collect a different kind of bitmap in which the Hamming distance between the block and the peak bitmap is less than a pre-defined threshold. The length of the secret message is computed from the total number of bitmaps in the candidate list. The scheme converts the secret message to form an indicated index and uses the corresponding indicated bitmap in the candidate list to replace the original bitmap. Experimentally, the proposed scheme has a high image quality, and the information hiding capacity can be adjusted by the threshold.